Global Call Center surpassing financial crisis - Oyanguren, Lyneth A. (School of Management, University of the Philippines Mindanao, 2011)
This Strategic Management Plan is a three-year plan for Global Call Center. Its objective is to create and determine the best strategies that shall address current difficulties which Global Call Center is facing. The conceptual framework used is an adaption both with F. David (2001) and J. Pearson (2000). The first Chapter includes the overview of the Company. A general situation review was conducted to determine the existing condition and challenges of the Company. On the other hand, the second and third Chapters are the external and internal factors that are directly and indirectly affecting Company?s performance. The Socio cultural, technological, economical, ecological, and regulatory of STER analysis and Porter?s Five Forces Model of Competitive Analysis are the primary tools in assessing company?s opportunities and challenges. The internal analysis however, used the interview discussion with the company?s officer-in-charge, employee satisfaction surveys to identify the strengths and weaknesses of the functional areas ? General Management, Human Resource, Finance, Operations and Marketing. Lastly, the (S) Strengths, (W) Weaknesses, (O) Opportunities and (C) Challenges served as the outline and the tool in identifying the core challenges and creation of strategies to surpass the crisis that they are facing. Based on the above findings and its proposed core values, vision, mission and goals, and the resulting strategies from SWOC Matrix ? using the influence of the internal strengths, lessening the internal weaknesses while exploiting the opportunities and addressing the external environment challenges, the more appropriate strategic choice is continuing the concentric strategy, followed by market development, and lastly the change strategy. The remaining chapters of this paper presents the policy guidelines for the functional areas which includes four (4) basic S components namely, the structure, systems, staff, shared values and performance that would support the aforementioned strategic choices. Finally, the last chapter presents the measure and control. This chapter specifies the action plan and monitoring plan for each strategic choice with the appropriate objectives; responsible person or unit, the resources, timeframe, performance indicators and key result areas and the evaluation are in place. The strategies are implemented within the 3 year operations starting from 2012-2014.